Influence of Solidification Microstructure on Mechanical Properties of Al0.8CrCuFeNi2 High Entropy Alloy - Zollinger, Julien; Fleury, Eric (Frontiers in Materials, 2020)
The solidification microstructure of Al0.8CrCuFeNi2 high entropy alloy consists of primary fcc dendrites decorated with interdendritic bcc and B2 phases. In this work the mechanical properties obtained for columnar oriented growth and equiaxed microstructures are compared. Highest properties are obtained for columnar structures when loading is parallel to the growth direction due to confinement of the deformation inside the columnar dendrite trunks.